2001
DOI: 10.1023/a:1013036732691
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Genes from the biocontrol fungus Trichoderma atroviride encoding the antifungal proteins endochitinase or exochitinase (N-acetyl-beta-D-hexosaminidase) were inserted into 'Marshall McIntosh' apple singly and in combination. The genes were driven by a modified CaMV35S promoter. The resulting plants were screened for resistance to Venturia inaequalis, the causal agent of apple scab, and for effects of enzyme expression on growth. Disease resistance was correlated with the level of expression of either enzyme whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(34 citation statements)
references
References 13 publications
4
30
0
Order By: Relevance
“…Even though similar results have been obtained by Lorito et al [8] in tobacco, a negative correlation between the level of an endochitinase gene solely and endo-and exochitinase genes combined on growth of apple transgenic plants was registered in two previous papers by Bolar et al [10,11].…”
Section: Evaluation Of Transgenic Tobacco For the Presence Of Transgesupporting
confidence: 77%
See 2 more Smart Citations
“…Even though similar results have been obtained by Lorito et al [8] in tobacco, a negative correlation between the level of an endochitinase gene solely and endo-and exochitinase genes combined on growth of apple transgenic plants was registered in two previous papers by Bolar et al [10,11].…”
Section: Evaluation Of Transgenic Tobacco For the Presence Of Transgesupporting
confidence: 77%
“…Lorito et al [8] reported the correct post-translation processing of secretion signal peptides belonging to chitinases from T. harzianum and tomato when expressed in tobacco plants. Conversely, Bolar et al [11] found an inefficient splicing in exochitinase transcripts from T. atroviride in apple plants.…”
Section: Evaluation Of Transgenic Tobacco For the Presence Of Transgementioning
confidence: 94%
See 1 more Smart Citation
“…Chitin-degrading enzymes such as chitinase and NAHA, both alone or in combination, can also confer resistance to insects (Lawrence and Novak 2006;Dowd et al 2007a) and plant pathogens (Bolar et al 2000(Bolar et al , 2001. Moreover, they can increase levels of disease resistance in maize and other plants when expressed transgenically ).…”
Section: Insect Resistance Genesmentioning
confidence: 99%
“…The authors hypothesized that pyramiding both genes, each with a relatively low level of expression, may lead to high resistance whilst retaining good vigor. Transgenic lines with both genes (low ech42 and high Nag 70 expression) had a high level of scab resistance without significant growth reduction [49]. The authors reported that selected lines were evaluated in the field for resistance, growth, and fruit quality; however, no data are currently published.…”
Section: Fungal Disease Resistancementioning
confidence: 99%